2002
DOI: 10.1111/j.0016-7398.2002.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of transboundary water resources: lessons from international cooperation for conflict prevention

Abstract: Tensions over freshwater resources may become more frequent as pressures on water resources grow due to increased demand and variability of rainfall. Conflicts may take place between or within countries or between competing sectoral users. This paper focuses on institutional approaches for enhancing cooperation between countries for sustainable development of transboundary freshwater bodies and contributing basins. It is assumed that instead of being zones of conflict, shared water resources can provide a basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 0 publications
0
58
0
1
Order By: Relevance
“…In this way, the exchange of water resources data and information can provide a first step toward broader transboundary cooperation and agreement formation (Kliot and Shmueli 1997;Miles et al 2002;Uitto and Duda 2002). Reliable knowledge about negative transboundary consequences of a problem, for example, is essential for creating sustainable international policy agreements to address the problem (Dimitrov 2006: 18).…”
Section: Advantages Of Data and Information Exchangementioning
confidence: 99%
“…In this way, the exchange of water resources data and information can provide a first step toward broader transboundary cooperation and agreement formation (Kliot and Shmueli 1997;Miles et al 2002;Uitto and Duda 2002). Reliable knowledge about negative transboundary consequences of a problem, for example, is essential for creating sustainable international policy agreements to address the problem (Dimitrov 2006: 18).…”
Section: Advantages Of Data and Information Exchangementioning
confidence: 99%
“…A significant portion of the world's watersheds straddle jurisdictional boundaries where political and hydrological boundaries often do not correspond [1]. Particular challenges relating to resource management in such transboundary contexts include differing legal and regulatory frameworks, languages, economic conditions, political history and antecedents with public participation, and stakeholder organizations [2].…”
Section: Introductionmentioning
confidence: 99%
“…When analysing cooperative, transboundary ecosystem management initiatives across the Canada-US border, Hildebrand et al [39] found success relied on participating jurisdictions exploring commonalities and developing a shared set of objectives and action plans to address common issues. These objectives and plans provide the underpinning for joint action, resulting in the resolution of transboundary issues [39].Developing strategic projects was found to be a useful way of getting participating countries to focus on one or two key issues and was more beneficial than trying to get participants to instigate a broad collaborative campaign [40]. Strategic joint fact-finding among neighbouring jurisdictions injects impetus, political buy-in and participation into the transboundary planning initiative [40].…”
Section: Shared Experiences Common Issues and Joint Solutionsmentioning
confidence: 99%
“…These objectives and plans provide the underpinning for joint action, resulting in the resolution of transboundary issues [39].Developing strategic projects was found to be a useful way of getting participating countries to focus on one or two key issues and was more beneficial than trying to get participants to instigate a broad collaborative campaign [40]. Strategic joint fact-finding among neighbouring jurisdictions injects impetus, political buy-in and participation into the transboundary planning initiative [40]. The use of the initial strategic projects can strengthen confidence in inter-jurisdictional working relations, eliminate obstacles to collaborative factfinding and develop capacity among different actors within each nation [41].…”
Section: Shared Experiences Common Issues and Joint Solutionsmentioning
confidence: 99%